A contribution to the knowledge of charophytes in Myanmar; morphological and genetic identification and ecology notes. Issue 1 (2nd January 2021) - Mjelde, Marit; Swe, Thida; Langangen, Anders; Ballot, Andreas
ABSTRACT: Information on the distribution and species composition of charophytes in Myanmar is scarce. Only a few studies on charophytes in ponds were conducted in Myanmar at the end of the nineteenth and first half of the twentieth century and lake habitats were not included in these studies. To increase the knowledge, we investigated Chara spp. from seven Myanmar lakes and reservoirs. In a polyphasic approach using morphological traits and DNA barcoding the specimens found were classified as Chara zeylanica and Chara fibrosa. Chara zeylanica is the most common of the two species found in Myanmar and was observed in five lakes, while Chara fibrosa was only found in three lakes. Chara zeylanica seems to prefer calcareous lakes while C. fibrosa was found in both highly and moderate alkaline lakes. Both species were recorded in low-impacted lakes only, with total phosphorous (TP) concentrations below 20 µg L −1 . Increased human impact on freshwater habitats must therefore be considered as a factor reducing Chara biodiversity in Myanmar.